Make a desert and call it peace: the march of online reverse auctions in business markets - Araujo, Luis (2022)
This paper explores the effects of online reverse auctions (ORAs) in business markets using an illustrative case study of the introduction of this tool in relationships involving a car assembler and three of its suppliers. In an online reverse auction, a buyer defines the terms of the exchange and sellers bid to push the prices down either through open or sealed bid formats. The feasibility of these auctions depends on the precise qualification of what sellers have to bid for so as to enable perfect comparability of prices. In practice, it as difficult to codify all the necessary information required to generate specifications as it is to separate the process of formulating solutions from their implementation. Whereas relational contexts tolerate these ambiguities and grey zones, tools such as ORAs require precise specifications and clear distinctions between the objects to be transacted and phases of the transaction. Our empirical data shows how actors work around these difficulties and cope with the constraints imposed by ORAs. The paper concludes that online reverse auctions have a number of intended and unintended consequences for buyer-supplier relationships as well as for the relationship the purchasing and technical functions within the buying organisation